A dog's life : the autobiography of a stray - Martin, Ann M., 1955- (New York : Scholastic, 2005)
Squirrel, a stray puppy, tells her life story, from her nurturing mother and brother to making her own way in the world, facing busy highways, changing seasons, and humans both gentle and brutal.
Keywords: Dogs -- Fiction; Orphaned animals -- Fiction